Enhancing Awareness of Healthy Lifestyles to Prevent Obesity in Women of Reproductive Age: A Study at Perbarakan Village - Ika Nur Saputri; Nurianti, Irma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Currently, nutritional problems remain a significant public health concern in Indonesia. Economic conditions and increased food consumption levels among the population have contributed to the rising prevalence of obesity. Obesity is a nutritional disorder characterized by excessive fat accumulation in the body. This condition leads to abnormal fat distribution, resulting in decreased muscle mass, quality, and strength. The development of obesity is influenced by poor lifestyle habits, genetic predisposition, and hormonal imbalances. This community service program (PkM) aimed to educate the public on strategies to reduce the risk of obesity by promoting the adoption of healthy lifestyles. The intervention specifically targeted women of reproductive age (WRA), encouraging them to improve their lifestyle practices to prevent obesity-related complications. The program was delivered through lectures, active discussions, and practical field sessions, with a total of 30 participants.During the activity, the PkM team provided health education materials, facilitated interactive question-and-answer sessions, and conducted hands-on training. As a result, there was a significant increase in both knowledge and practical skills among participants. The findings showed a 30-point (51.4%) increase in participants’ knowledge, and 97% of them expressed a strong commitment to adopting healthier behaviors. Moreover, 97% of participants reported high satisfaction with the program, citing the usefulness of the content, engaging materials, and effective delivery methods.This PkM initiative demonstrated its effectiveness in enhancing knowledge and shaping positive attitudes among women of reproductive age regarding healthy lifestyle practices to prevent obesity.